2019
DOI: 10.1186/s12874-019-0662-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of the spiritual care-giving scale (C-SCGS) in nursing practice

Abstract: BackgroundSpiritual care is defined as recognizing and responding to the needs of the human spirit when the individual is facing trauma, illness, or sadness. Providing spiritual care is one of the core aspects of holistic care, as it is significantly associated with patients’ quality of life. The provision of optimal spiritual care requires good understanding by the nurses. Therefore, it is important to assess this understanding by using a proven, well-validated instrument. The Spiritual Care-Giving Scale (SCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Therefore, the fixed factor method was used as the criterion to decide the number of dimensions, and an EFA was conducted to test whether the items were consistent with the pre-defined sub-dimensions of the questionnaire (item homogeneity). Based on the results, inconsistent items were removed [13] (items were inconsistent with the predefined sub-dimensions; low factor loadings, i.e., < 0.70; low total Cronbach's alpha if the item was deleted; and low item-questionnaire correlations, i.e., < 0.40), and those items that best reflected the definition and theoretical dimensions of the perceived professional benefits described above were retained. The subsequent items were re-rotated after the removal of items following the factor analysis.…”
Section: Stepsmentioning
confidence: 99%
“…Therefore, the fixed factor method was used as the criterion to decide the number of dimensions, and an EFA was conducted to test whether the items were consistent with the pre-defined sub-dimensions of the questionnaire (item homogeneity). Based on the results, inconsistent items were removed [13] (items were inconsistent with the predefined sub-dimensions; low factor loadings, i.e., < 0.70; low total Cronbach's alpha if the item was deleted; and low item-questionnaire correlations, i.e., < 0.40), and those items that best reflected the definition and theoretical dimensions of the perceived professional benefits described above were retained. The subsequent items were re-rotated after the removal of items following the factor analysis.…”
Section: Stepsmentioning
confidence: 99%
“…The original 35-item SCGS was developed by Tiew and Creedy [26] to measure nursing students' and nurses' perceptions of spirituality and spiritual care. We translated and evaluated the 34-item C-SCGS [27] with Tiew's permission. The C-SCGS has four core factors: attributes of spiritual care (Cronbach's alpha 0.941), definitions of spirituality and spiritual care (Cronbach's alpha 0.852), spiritual perspectives (Cronbach's alpha 0.836), and spirituality and spiritual care values (Cronbach's alpha 0.866).…”
Section: Additional Measurement Instrumentsmentioning
confidence: 99%
“…Motivated by the growing importance placed on the provision of spiritual care to patients, research on spiritual care has recently increased [34]. However, although previous research has shown that both patients and their family members have great spiritual needs and that medical personnel must show concern for and satisfy these needs, this issue has not received sufficient attention in nursing practice [37,62].…”
Section: Clinical Relevancementioning
confidence: 99%
“…Under this care, patients can explore strategies to overcome their illnesses as well as strengthen their physical, social, and psychological health, thereby improving their quality of life and state of health [17,23,31,32]. Spiritual care is a core element of holistic nursing and has already been incorporated into nursing education and practice [33][34][35][36]. In addition, the ability to provide spiritual care to patients is increasingly considered a major occupational skill for nurses [19,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation